Pilosidade púbica na criança e hiperplasia congénita supra-renal não clássica. - A Mota; G Fonseca; I Rebelo; M E Crespo (Acta Médica Portuguesa, 1991)
Before the age of 8 in females and 9 in males, the presence of pubic hair can be the first sign of a gonadal or adrenal disease. In order to identify the late onset type of congenital adrenal hyperplasia in premature pubescence, we did the adrenal short stimulation test with Synacthen, on 30 children. Five girls and one boy showed a 21-hydroxylase deficiency, in which the seric 17-OH Progesterone at 60 minutes is 28.8 +/- 15.2 ng/ml, being in a control group 2.30 +/- 0.8 ng/ml [p less than 0.01]. The 20% incidence we have found, justifies the testing of every premature pubescent child.